Inculturation of Plenat Nim for the life of the community of Timorese believers in Soe, East Nusa Tenggara, Indonesia - Selan, Yunus (Practical theology, 2025)
This research aims to examine the inculturation of Plenat Nim by Timorese. The research focuses on the believers of Timorese, who still practice specific prayer rituals to respect their parents after the death of their parents as obedience to God's fifth commandment. It was known as Nanonob Sin Lasi atau Piu Sin Lasi before the Gospel reached Soe, but after they knew the Gospel, they changed its name to Plenat Nim. These rituals prioritize the spirits of the deceased as having the power to grant forgiveness, blessings, serenity, and safety in their daily lives. Timorese believe these rituals help maintain a harmonious relationship between the living and the dead. The Timorese people view these prayer rituals as essential to their cultural identity and continue to pass them down from generation to generation. The research methodology employed in this research is fild study with analysis through the lens of inculturation approach. The data collection is through processes such as collecting, reducing, displaying, drawing conclusions, and verification. The Authors present all data findings descriptively. The research revealed that Timorese believers still have faith in the power of the dead to bless, help, and heal the living.